TINJAUAN HUKUM PELEPASAN HAK ATAS TANAH KAS DESA OLEH PT.PERTAMINA (PERSERO) DALAM PENGEMBANGAN DEPOT PENGISIAN PESAWAT UDARA (DPPU) ADI SUMARMO SOLO - Dewi Puji Astuti, Chalida Fatma Ferani (MAJALAH ILMIAH GEMA, 2014)
Legal position on the problem of land is usually done by means of negotiations between the two sides, more particularly the problem of the liberation of the country Ngesrep cash that will be used for expansion Filling Aircraft Depot (DPPU) Adi Sumarmo Solo, the parties negotiate, ie between the from PT.Pertamina with village leaders Ngemplak where in the process of land acquisition through the stages long enough from the location setting, counseling, negotiation, identification, inventory, valuation of land price appraisal by the board or the board of assessors, compensation decisions, to emission rights. For through the stages it takes quite a long time up to 439 days the details stated in Law No. 2 Year 2012 Viewed from the angle of its own legal research, then in this study the authors use different types of normative legal research, research capacity and prescriptive approaches law. PT.Pertamina and The Village Ngesrep as the party that will do the release land release process is not implemented in accordance with the law. The process of land release cash Ngesrep village is neither party must include Lands Board (BPN) in cash land clearing procedures this village, it was assessed that both the mengesampibgkan an important role in the release of government land. Moreover in the case of setting the magnitude of change in the form of land loss is the successor, the Countryside or Appraiser PT.Pertamina not use that in this case comes from the Board of Lands. It is feared would adversely affect later on because in fixing the compensation shall only based on the price of land around. Keywords: Relief Lands, Land Kas Village, Indemnification and Release of Land, Land Clearance Procedures